2009
DOI: 10.1002/clc.20297
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intra‐aortic Balloon Pump Using Glycoprotein IIb/IIIa Antagonists

Abstract: Background: Anticoagulation with heparin is recommended with intra-aortic balloon pump (IABP) to prevent thrombosis and embolization. However, anticoagulation increases the risk of bleeding, particularly in combination with glycoprotein (GP) IIb/IIIa antagonists. Hypothesis: We investigated the safety of using GP IIb/IIIa antagonists without heparin after IABP insertion in patients who underwent primary percutaneous coronary intervention (PCI). Methods: Consecutive patients with acute myocardial infarction (AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…In our study the rate of ischemic complications was 2.6% and the rate of minor bleeding complications was 4.2%. These findings are in accord with the complication rates of previous studies 5–11 . There was no difference concerning vascular complications in Group I (<24 hours following surgery) and Group II (>24 hours following surgery).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study the rate of ischemic complications was 2.6% and the rate of minor bleeding complications was 4.2%. These findings are in accord with the complication rates of previous studies 5–11 . There was no difference concerning vascular complications in Group I (<24 hours following surgery) and Group II (>24 hours following surgery).…”
Section: Discussionsupporting
confidence: 92%
“…While they found no differences in ischemic complications, bleeding from the puncture site was more common in the heparin‐treated patients. Laish‐Farkash et al 10 reported a 3.1% rate of ischemic complications and a 9% rate of major bleeding complications in patients following primary percutaneous coronary intervention treated with both aspirin and glycoprotein IIb/IIIa antagonists without heparin. However, Chin et al 11 compared patients from the Benchmark Counterpulsation Outcomes Registry who received and did not receive anticoagulation therapy during IABP, and reported that anticoagulation was associated with a lower mortality rate (18.2% vs. 15.5%, respectively) and less limb ischemia (3.2% vs. 2.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…1,10 As in the study by Bream-Rouwenhorst et al, we found that the degree of platelet count reduction was greater among patients with HIT than among those without HIT. 1 Because of the important clinical implications of this diagnosis, this finding suggests that IABP patients who are receiving heparin and who have a marked reduction in platelet count (>50%) should be considered for HIT testing.…”
Section: Discussionsupporting
confidence: 68%
“…After applying inclusion and exclusion criteria, 16 articles remained eligible for meta-analysis, of which 13 were prospective studies and 3 were retrospective studies. [13][14][15][16][17][18][19][20][22][23][24][25][26][27][28][29] Eight studies were excluded because no control arm was available, 30 no mortality data were available, [31][32][33][34] or there was different timing of outcomes. [35][36][37] Thus, the systematic literature search for studies comparing the effects of IABP with no IABP in patients with AMI, with or without cardiogenic shock using aforementioned criteria revealed a total of 16 studies (N ¼ 11 778).…”
Section: Literature Searchmentioning
confidence: 99%